The Efforts of the Caretaker of the Child Welfare Institution (CWI) Suara Hati Sidoarjo in Overcoming the Delinquency of Foster Children: Upaya Pengasuh Lembaga Kesejahteraan Sosial Anak (LKSA) Suara Hati Sidoarjo dalam Menanggulangi Kenakalan Anak Asuh - Hasrin Mar'atusshifa; Istikomah Istikomah (Academia Open, 2022)
Various problems that occur in foster children in the form of juvenile delinquency problems that have an impact on the behavior of foster children at LKSA Suara Hati Sidoarjo make caregivers who have the responsibility to deal with foster children's delinquency. The purpose of this article is to find out how the efforts of LKSA Suara Hati Sidoarjo caregivers in dealing with foster children's delinquency and what obstacles are encountered by LKSA Suara Hati Sidoarjo supervisors in dealing with foster children's delinquency. The method used is descriptive qualitative method using the method of observation, interviews, and documentation. The results of the efforts made by LKSA Suara Hati Sidoarjo caregivers in overcoming the delinquency of foster children are by taking (a) preventive (prevention), (b) curative (healing), and (c) coaching. As well as the obstacles found are (a) dishonesty in foster children, (b) influences from the outside environment, (c) lack of support from guardians or foster children's families.